Spatial-temporal analysis of urban-rural differences in the development of elderly care institutions in China - Li, Xiang; Li, Chen; Huang, Yi (Frontiers in Public Health, 2022)
Background Aging is both a sign of rising life expectancy per capita and social progress, and a challenge for society. Due to the decline in physiological functions, the rate of illness has increased significantly, leading to a rise in demand for healthcare, life care and other elderly care. With the overlapping impact of an aging population, advanced aging, empty nesting families and the weakening of traditional elderly care functions, the issue of elderly care for the empty nesters, the elderly alone and the disabled has become more prominent and has become a focal point of concern for all sectors of society. As an important supplement to the elderly care service system, institutional care, together with home care, community care and rural care, are mutually complementary. Methods The study establishes a panel database of urban and rural elderly-care institutions in 276 cities from 2010 to 2016, and uses comprehensive measurements to reveal the spatial-temporal changes of urban and rural elderly care institutions in China. Results First, in terms of spatial pattern, the overall score of elderly care institutions in urban areas shows a “double-high” spatial pattern of higher scores in coastal areas than inland areas, and higher scores in urban areas than in rural areas. In terms of the differences in the scores of secondary indicators, the eastern urban areas have higher scores than the rural areas for the indicators of facilities construction and nursing staff of elderly institutions, while the eastern rural areas have higher scores than their urban counterparts for the indicators of service recipients of elderly institutions. Second, in terms of temporal change, there is a clear “urban progress and rural regression” in the evolution of China's elderly care institutions. Third, in terms of spatial and temporal evolution, there is a clear spatial autocorrelation in the composite scores of urban and rural elderly care institutions in China, and the spatial autocorrelation of the composite scores of elderly care institutions shows a clustering pattern. Discussion The contradiction between the limited ability to pay of the elderly people staying in elderly care institutions and the huge demand for elderly care services is bound to affect the sustainability of the development of public elderly care institutions in both urban and rural areas. Due to historical factors, the marketisation of elderly care institutions in China started late and the marketisation of elderly care is not high. As the population ages, China's elderly-care institutions have begun to transform from public institutions of a welfare nature to those with some market mechanisms, but the overall transformation has been slow, resulting in the service guarantee system of elderly-care institutions lagging far behind the actual needs of the elderly. The long-term development of elderly care institutions must introduce market mechanisms, enhance the endogenous dynamics of elderly care institutions, correctly handle the relationship between fairness and efficiency of elderly care services, and improve the professionalism, income and treatment of elderly care staff while compensating for the lack of development of elderly care institutions and the inadequate layout of space, so as to continuously improve the service quality of elderly care institutions.